Sensory and microbiological quality of a baked product containing xylitol as an alternative sweetener - Winkelhausen, E., 10 (3) 639-649 (2007).; Jovanovic-Malinovska, R.; Velickova, E.; Kuzmanova, S (Taylor and Francis, 2007)
The potential application of xylitol, as low energy alternative sweetener, was investigated in baked products. Xylitol was used as sole sweetener in home made cookies, the properties of which were compared to products containing sucrose and glucose. The sensory properties were evaluated by discrimination, descriptive, and affective tests. The storage time of one and two weeks, both at 4–6°C and at 20–22°C did not show significant impact on the flavor and texture properties of all cookies. After being stored for 3 months at 20–22°C, the samples with sucrose showed statistically significant differences in crunchiness (P < 0.001) and tenderness (P < 0.01). The cookies prepared with xylitol, apart from significantly reducing the aftertaste (P < 0.001), did not exhibit any other significant changes. Statistically significant differences (P < 0.001) were detected between the samples containing sucrose and xylitol in all texture attributes and in the cooling effect, but no difference in the sweetness was observed. The most chosen categories on the hedonic scale for the xylitol cookies were “like slightly” and “like moderately,” while the extreme categories were not ascribed. Compared to the cookies with sucrose and glucose, xylitol cookies had least microbial loads at different storage and temperature regimes and were microbiologically safe with tendency to have longer shelf-life than the other products